The moral status of human embryo-like structures: potentiality matters? - Sawai, T; Minakawa, T; Pugh, J; Akatsuka, K; Yamashita, JK; Fujita, M (EMBO Press, 2020)
New techniques to generate and culture embryo-like structures from stem cells require a more fine-grained distinction of potential to define the moral status of these structures.